PELESTARIAN CAGAR BUDAYA KOTA PAREPARE MELALUI PENGELOLAAN WEBSITE - Siri, Hasnani; Muhammadun, Muzdalifah; Ramli, Nurleli (Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract Preserving cultural heritage is something that needs to continue to be implemented so that regional identity is not forgotten. Utilizing website is a form of preservation that is in line with current developments. Website management must of course be accompanied by experts to provide assistance regarding management techniques and interesting content. Apart from that, synergy is also needed with the parepare city government to strengthen information regarding culture heritage sites that are still worthy of preservation. The targets of service are student of the history of Islamic civilization study program by providing direct assistance to them using a PAR (Participatory Action Research) approach using lecture, discussion, and trial techniques. The results of the mentoring show the students’ ability to manage a website by entering accurate information about parepare citys’ cultural heritage sites and the website can be accessed by the general public.